The Role of Local Self-government Units in the System of the Organization and Financing Local Public Transport - Krzysztof Czarnecki (Prawo Budżetowe Państwa i Samorządu)
The article describes the system of organization and financing of the local public transport in Poland. Providing local public transport is one of the tasks of local self-government units (called gmina). According to The Act on Public Transport of 2010 that task may be performed using different legal forms, e.g. budgetary entities or commercial companies established by local self-governments.